EDUKASI ANEMIA PADA REMAJA PUTRI DI DESA WATUGEDE - Anis Setyowati; Wahyu Wijayati (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
Anemia is a nutritional problem that is widely found throughout the world and does not only occur in developing countries but also in developed countries. Adolescent girls have a ten times greater risk of suffering from anemia compared to young men. The purpose of this service activity is to increase the percentage of young women who consume blood-added tablets in Watugede Village. The method used is focus group discussions and lectures. The results showed that there was an increase in the percentage of consumption of FE tablets after being given education on the criteria for routine consumption from before education by 24.44% to 46.67%. This shows that education about anemia in adolescents can increase adolescent knowledge about anemia, and have a positive impact on changes in behavior in consuming blood-added tablets.